Pengaruh Social Media Marketing TitTok, Brand Awareness, Harga dan Promosi Terhadap Keputusan Pembelian skincare made in Indonesia di Timor-Leste - Sanches, Olandina de Jesus; Susyanti, Jeni; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Digital technology and social media, especially TikTok, have changed the way people buy skincare products. This study looks at how TikTok marketing, brand awareness, price, and promotions affect the buying choices of Gen Z Indonesians in Timor-Leste for skincare products. The research used a survey with 112 people from Gen Z who had either watched or bought Indonesian skincare products on TikTok. They used SPSS to do multiple linear regression analysis. The results showed that all four factors—TikTok marketing, brand awareness, price, and promotions—positively and significantly influence purchasing decisions. The findings highlight the need for creative TikTok campaigns, good brand awareness, fair pricing, and appealing promotions to attract young consumers in global markets. Keywords: Social Media Marketing, Brand Awareness, Price, Promotion, Purchasing Decisions